2009
DOI: 10.1002/pros.21090
|View full text |Cite
|
Sign up to set email alerts
|

Three conformational antibodies specific for different PSMA epitopes are promising diagnostic and therapeutic tools for prostate cancer

Abstract: Due to their specific binding characteristics, the anti-PSMA mAbs 3/A12, 3/E7, and 3/F11 show great promise for diagnostic and therapeutic applications in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Binding inhibition of the scFv hD7-1(VL-VH) with the parental murine anti-PSMA mAb 3/F11 proved that the scFv retained binding to the same PSMA epitope. No binding inhibition was seen with the anti-PSMA control mAb J591, which is known to bind to a different PSMA epitope ( Figure 2D) (8). Due to its strong and specific PSMA binding, the scFv hD7-1(VL-VH) was identified as a suitable candidate for the construction of the immunotoxins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding inhibition of the scFv hD7-1(VL-VH) with the parental murine anti-PSMA mAb 3/F11 proved that the scFv retained binding to the same PSMA epitope. No binding inhibition was seen with the anti-PSMA control mAb J591, which is known to bind to a different PSMA epitope ( Figure 2D) (8). Due to its strong and specific PSMA binding, the scFv hD7-1(VL-VH) was identified as a suitable candidate for the construction of the immunotoxins.…”
Section: Resultsmentioning
confidence: 99%
“…The scFv D7 was derived from our murine monoclonal antibody (mAb) to PSMA 3/F11 (8,9). The PE40 domain consists of the structural domains II, Ib and III ( Figure 1).…”
mentioning
confidence: 99%
“…Silver et al (1) and Mhawech-Fauceglia et al (25) found no expression in the parotids. However, PSMA RNA has been found in salivary glands (26), in tissue extracts (27), and by immunohistochemistry (28). A variety of mAbs binding to different epitopes of the extracellular domain of PSMA presented with different stainings of normal tissues (28)-a possible indicator that different splicing variants of PSMA may exist.…”
Section: Discussionmentioning
confidence: 99%
“…However, the transferred cells could be only detected at the injection site and not systemically. An optimization of our cell-labeling approach might involve mAb fragments (26,27), which carry fewer radionuclides, and thus induce less damage to their target cells. Furthermore, the missing Fc-part of the mAbs would likely prevent the Fcreceptor-mediated cellular cytotoxicity in vivo, thereby increasing the safety of a possible clinical translation.…”
Section: Discussionmentioning
confidence: 99%